Bonheur en boule: an adapted group-based physical activity program for youth with disabilities - D’Amours, Jason; Girard, Stéphanie; Miquelon, Paule; Veillette, Pierre-Luc (Frontiers in Sports and Active Living, 2025)
IntroductionYouth with disabilities face significant barriers to physical activity (PA) participation, despite its documented benefits across cognitive, social, affective, and physical domains. Physical literacy (PL) and self-determination theory (SDT) offer complementary frameworks for designing adapted PA programs that foster autonomy, competence, and relatedness. However, limited research integrates both frameworks in adapted PA programs. This study evaluates the impact of Bonheur en boule (BEB), an adapted group-based PA program, on basic psychological needs, global self-esteem, and PA intentions of youth with disabilities while also assessing parental satisfaction.MethodsA mixed-methods approach was used. Eleven youth (Mage = 13.27, SD = 5.42) with various disabilities participated in the BEB program, consisting of two 15-week sessions of adapted Dek Hockey (Ball hockey). Quantitative measures assessed participants' basic psychological needs (autonomy, competence, relatedness), global self-esteem, and PA intentions at three time points. Non-parametric tests (Friedman and Wilcoxon signed-rank) were used for statistical analyses. Parent satisfaction was evaluated through semi-structured interviews, analyzed using content analysis.ResultsSignificant improvements were observed across all three basic psychological needs and global self-esteem. Competence and autonomy satisfaction increased notably between the first and second time points (p < 0.01), while global self-esteem improved later in the program (p < 0.01). All participants (n = 11) expressed intentions to continue both PA and the program. Parental feedback highlighted positive changes in children's cognitive (e.g., attention, problem-solving), social (e.g., friendships, teamwork), affective (e.g., emotional regulation, confidence), and physical (e.g., motor skills, endurance) development. Parents also valued the program's inclusive approach and flexibility.DiscussionFindings suggest that an SDT and PL based PA program can foster satisfaction of basic psychological needs leading to self-determination, increase global self-esteem and support PA engagement among youth with disabilities. The program's structure, emphasizing autonomy, competence, and social connections, contributed to participant development. Parents' strong appreciation underscores the program's perceived effectiveness. However, challenges such as small sample size and the lack of a control group limit generalizability.ConclusionBEB demonstrates the feasibility of an adapted PA program rooted in SDT and PL principles, showing promising outcomes for youth with disabilities. Future research should explore long-term behavioral impacts and broader implementation strategies.